-24=6(7x+3)

Simple and best practice solution for -24=6(7x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24=6(7x+3) equation:


Simplifying
-24 = 6(7x + 3)

Reorder the terms:
-24 = 6(3 + 7x)
-24 = (3 * 6 + 7x * 6)
-24 = (18 + 42x)

Solving
-24 = 18 + 42x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42x' to each side of the equation.
-24 + -42x = 18 + 42x + -42x

Combine like terms: 42x + -42x = 0
-24 + -42x = 18 + 0
-24 + -42x = 18

Add '24' to each side of the equation.
-24 + 24 + -42x = 18 + 24

Combine like terms: -24 + 24 = 0
0 + -42x = 18 + 24
-42x = 18 + 24

Combine like terms: 18 + 24 = 42
-42x = 42

Divide each side by '-42'.
x = -1

Simplifying
x = -1

See similar equations:

| 23/6x | | cot(sin)=cos | | .9x+11.5=24.1 | | 22/3+3n=4/5+12 | | 17+5=5+n | | 0.10x+0.12(x+1500)=642 | | 8x+5x-3=23 | | x(x)+5x=9x+12 | | 28+21x=42+14x | | 4(2x-3)=5(x-2) | | -15-10f=-10f-15 | | 35-8x=47 | | 8(x-1)+3(x+4)=48 | | 7x+4=5x-6x+10 | | -1/2*5 | | 8(4.6)-6=2(4.6+11) | | 8(4.6)-6=2(4.7+11) | | 36x^3=8x | | 3(x+2)+4x-5=7x+1-6 | | -6(5.61x-3.21)=4.7 | | k-1=4k+8 | | =X+17 | | 5-2x/5-3x+6/2=x-7 | | ax-x=cforx | | -1/2(5x-8)=7 | | 8-(2a-2)+4=4 | | W^2=64/49 | | Y=mx+bsolvem | | 4(2p-3r+12)-5(p+r+11)=3p-17r-7 | | 12x+5x-18=2x-12 | | -6+5(9+X)=44 | | 54=-16x^2+64x+6 |

Equations solver categories